2006
DOI: 10.1021/jm0605482
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Aminoquinazolines as Potent, Orally Bioavailable Inhibitors of Lck:  Synthesis, SAR, and in Vivo Anti-Inflammatory Activity

Abstract: The lymphocyte-specific kinase (Lck) is a cytoplasmic tyrosine kinase of the Src family expressed in T cells and natural killer (NK) cells. Genetic evidence in both mice and humans demonstrates that Lck kinase activity is critical for signaling mediated by the T cell receptor (TCR), which leads to normal T cell development and activation. Selective inhibition of Lck is expected to offer a new therapy for the treatment of T-cell-mediated autoimmune and inflammatory disease. Screening of our kinase-preferred col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…These findings highlight an alternative binding mode for this approved kinase drug and reveal a new resistance mechanism for c-Kit A-loop mutants [51,52] . [49] 1irk RTK SRC [66] 2oiq CTK IGFR [61] 2oj9 RTK CSK [65] 1byg CTK VEGFR2 [67] 2oh4 RTK AMPK2a * [68] 2h6d CAMK c-KIT [59] 1t46 RTK MNK1 * [69] 2hw6 CAMK FLT-3 * [57] 1rjb RTK MNK2 * [70] 2ac3 CAMK FMS (CSFR) [60] 2i0y RTK p38 [40] 1kv2 CMGC EGFR [71] 2rf9 RTK CDK6 * [72] 1bi7 CMGC MUSK * [73] 1luf RTK AKT-2 * [74] 1gzk AGC TIE-2 [75] 2oo8 RTK AURA [76] 2c6e Other ABL [53] 1fpu CTK ASK1 [77] 2clq STE LCK [78] 2ofv CTK bRAF [79] 1uwh TKL The examples described above have similar orientations of the DFG Phe near the ATP site but the classification of DFG-out can have intermediate orientations between that found in the active form and these examples. This is observed for the IGFR complex (2oj9) in which the DFG Phe is positioned out of the pocket to which it is bound in the active form but oriented away from the ATP binding region [61] .…”
Section: Structural Conceptsmentioning
confidence: 99%
“…These findings highlight an alternative binding mode for this approved kinase drug and reveal a new resistance mechanism for c-Kit A-loop mutants [51,52] . [49] 1irk RTK SRC [66] 2oiq CTK IGFR [61] 2oj9 RTK CSK [65] 1byg CTK VEGFR2 [67] 2oh4 RTK AMPK2a * [68] 2h6d CAMK c-KIT [59] 1t46 RTK MNK1 * [69] 2hw6 CAMK FLT-3 * [57] 1rjb RTK MNK2 * [70] 2ac3 CAMK FMS (CSFR) [60] 2i0y RTK p38 [40] 1kv2 CMGC EGFR [71] 2rf9 RTK CDK6 * [72] 1bi7 CMGC MUSK * [73] 1luf RTK AKT-2 * [74] 1gzk AGC TIE-2 [75] 2oo8 RTK AURA [76] 2c6e Other ABL [53] 1fpu CTK ASK1 [77] 2clq STE LCK [78] 2ofv CTK bRAF [79] 1uwh TKL The examples described above have similar orientations of the DFG Phe near the ATP site but the classification of DFG-out can have intermediate orientations between that found in the active form and these examples. This is observed for the IGFR complex (2oj9) in which the DFG Phe is positioned out of the pocket to which it is bound in the active form but oriented away from the ATP binding region [61] .…”
Section: Structural Conceptsmentioning
confidence: 99%
“…Because this site is directly adjacent to the site of ATP binding, it disrupts key interactions between a number of conserved catalytic residues and ATP. Since the initial characterization of Imatinib, a number of other inhibitors have been described that selectively bind the inactive conformations of other kinases [10,[31][32][33][34][35][36][37].…”
Section: Allosteric Kinase Inhibitorsmentioning
confidence: 99%
“…Immobilized analogs of indolinone SU6668 (31), gefitinib (32), pyrido [2, 3-d]primidine PP58 (33), bisindolylmaleimide GF109203X (34), aminopyrazole PHA36 and gwennpaullone have been used as affinity matrices to enrich for interacting proteins in cell lysates [106][107][108][109][110][111]. In all of these studies unexpected targets were identified that were later validated with biochemical techniques or activity assays.…”
Section: Cell Lysate Affinity Chromatographymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of compounds containing 2-morpholinoethanamine as a side group have shown a broad spectrum of biological activities, such as antigastroesophageal reflux disease and anti-irritable bowel syndrome [3], anti-inflammatory [4], and anticancer [5]. In our continuing interest for studying N-substituted ethylenediamine compounds [6], we were interested in this building block 1.…”
Section: Introductionmentioning
confidence: 99%